Lifestyle Medicine Reimbursement: A Proposal for Policy Priorities Informed by a Cross-Sectional Survey of Lifestyle Medicine Practitioners - Kelly J. Freeman (MDPI AG, 2021)
Lifestyle medicine (LM) is a rapidly emerging clinical discipline that focuses on intensive therapeutic lifestyle changes to treat chronic disease, often producing dramatic health benefits. In spite of these well-documented benefits of LM approaches to provide evidence-based care that follows current clinical guidelines, LM practitioners have found reimbursement challenging. The objectives of this paper are to present the results of a cross-sectional survey of LM practitioners regarding lifestyle medicine reimbursement and to propose policy priorities related to the ability of practitioners to implement and achieve reimbursement for these necessary services. Results from a closed, online survey in 2019 were analyzed, with a total of n = 857 included in this analysis. Results were descriptively analyzed. This manuscript articulates policy proposals informed by the survey results. The study sample was 58% female, with median age of 51. A minority of the sample (17%) reported that all their practice was LM, while 56% reported that some of their practice was LM. A total of 55% of practitioners reported not being able to receive reimbursement for LM practice. Of those survey respondents who provided an answer to the question of what would make the practice of LM easier (n = 471), the following suggestions were offered: reimbursement overall (18%), reimbursement for more time spent with patients (17%), more support from leadership (16%), policy measures to incentivize health (13%), education in LM for practitioners (11%), LM-specific billing codes and billing knowledge along with better electronic medical record (EMR) capabilities and streamlined reporting/paperwork (11%), and reimbursement for the extended care team (10%). Proposed policy changes focus on three areas of focus: (1) support for the care process using a LM approach, (2) reimbursement emphasizing outcomes of health, patient experience, and delivering person-centered care, and (3) incentivizing treatment that produces disease remission/reversal. Rectifying reimbursement barriers to lifestyle medicine practice will require a sustained effort from health systems and policy makers. The urgency of this transition towards lifestyle medicine interventions to effectively address the epidemic of chronic diseases in a way that can significantly improve outcomes is being hindered by current reimbursement policies and models.